A Substantive Theory of Decision-Making in Software Project Management - CUNHA, José Adson Oliveira Guedes da (2016)
Background: In software project management, the decision-making process is a complex set of tasks mainly based on human relations, individual knowledge, and cultural background. The factors that affect the decisions of Software Project Managers (SPMs), as well as their potential consequences, require attention because project delays and failures might be related to a series of poor decisions. Aims: To understand how SPMs make decisions based on how they interpret their experiences in the workplace. Further, to identify antecedents, moderators and consequences of those decisions to increase the effectiveness of project management. Method: Firstly, an exploratory study based on semi-structured interviews was conducted with SPMs from a large Brazilian governmental organization and from a small Portuguese private organization to shed light on the causal factors of SPMs’ cognitive biases and how they deal with them, including techniques and tools they used to minimize the cognitive biases’ adverse effects. The initial findings suggested that we needed a more grounded understanding of the mechanisms of decision-making. Thus, a broader research protocol based on semi-structured interviews was carried out with SPMs within a large Brazilian governmental organization and a large Brazilian private organization. We also conducted interviews with software engineers and PMO managers to triangulate the data, which was analyzed using techniques from grounded theory. Data from observations, document analysis and selected studies from a systematic literature review were also used. Results: We found that decision-making in software project management is based on knowledge sharing in which the SPM acts as a facilitator. This phenomenon is influenced by individual factors, such as experience, knowledge, leadership style, and skills, and by situational factors such as the autonomy of the SPM, task complexity and team members' technical competence. Conclusions: Due to the uncertainty and dynamism inherent to software projects, the SPMs focus on making, monitoring and adjusting decisions in na argument-driven way. Also, the involvement of the team members in decision-making aims to minimize the SPM's decision regret and cognitive biases as well as to maximize the team member's commitment.